Cirurgia bariátrica por laparoscopia : implicações econômicas para o Sistema Único de Saúde - Süssenbach, Samanta Pereira (2014)
The objective of this dissertation was to analyze some aspects related to the Roux-en-Y gastric bypass (RYGB) surgery access routes such as health effects, costs and possible diffusion of laparoscopy to the Brazilian National Public Health System (BNPHS). So, two papers were presented, aiming the comparison of the economic evaluation of both surgical routes (laparoscopy and laparotomy) and the evaluation of a possible diffusion rate of laparoscopy in the BNPHS. Article 1 was entitled "Systematic Review of the Economic Evaluation of Laparotomy versus Laparoscopy for Patients Who Underwent Roux-en-Y gastric bypass (RYGB) surgery" and aimed to analyze the cost-effectiveness of laparoscopic and laparotomic routes. The electronic databases used were MEDLINE, Embase, Scopus, Cochrane and Lilacs. From the 494 articles found, 6 met the inclusion criteria. All studies were published between 2001 and 2008 in the United States (USA). Three studies met less than half of the items that assessed the quality of results; two met five of the necessary items, and only one study met seven of 10 items. Five studies considered laparoscopic surgery the dominant strategy, because they presented higher clinical benefits (less likelihood of postoperative complications, shorter hospitalization) and lower total cost. This evaluation indicates that laparoscopy is a safe and well tolerated technique, although surgery costs are higher compared to laparotomy. However, the additional costs are offset by lower probability of complications after surgery. Article 2 was entitled "Implementing Laparoscopy in Brazil´s National Public Health System (BNPHS) – the Bariatric Surgeons´ point of view” and aimed to estimate 1) whether bariatric surgeons would support eventual incorporation of laparoscopy to the BNPHS; 2) whether there would be an increase in the total number of operations in case of availability of this option of access route; and 3) how would the redistribution of these two operation routes be. Using the Delphi method, we enlisted a panel of bariatric surgeons who answered a questionnaire previously developed for this purpose. In order to get a better consensus, two rounds were held. Of the 45 surgeons who attended a national event, 30 (66.7%) answered the Delphi questionnaire, which corresponded to the first round of the study. In the second, the final, round, 22 (48.9%) out of the 30 surgeons answered the questionnaire. Considering the possibility of incorporating the laparoscopic route in the BNPHS, approximately 95% of surgeons have expressed interest in choosing it. If the operation by laparoscopy was incorporated into the BNPHS, there would be a total average increase of 25% in the number of surgeries performed. So, in this new configuration system, the distribution of surgical procedures would be as follow: 62.5% and 37.5% by laparoscopy and laparotomy respectively. In conclusion 1) there was preference for laparoscopic route; 2) there would be an increase in the number of surgeries performed; and 3) the distribution of surgical procedures would be 62.5% by laparoscopy and 37.5% by laparotomy.